2021
DOI: 10.1002/sia.7053
|View full text |Cite
|
Sign up to set email alerts
|

The influence of Ti plasma etching pre‐treatment on mechanical properties of DLC film on cemented carbide

Abstract: The pre-treatment of substrate surface had been a key part of DLC film preparation to improve mechanical and tribological properties. Ti plasma etching pre-treatment was investigated in this paper as a new effective surface pre-treatment method to substitute transition layer. This pre-treatment used high-energy Ti plasma to impact substrate surface. Ti plasma etched the substrate to a depth of 407 nm and increased the roughness from 1.36 to 40.39 nm. A trace layer of substrate, together with cobalt, oxides, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…The Ti interlayer exhibits a dense and compact columnar structure from a partially enlarged zone on the bottom left corner of Figure 6C. increases to 0.019 μm at 330 V. It is found that the higher the sp 3 content is, the smaller the surface roughness is. The deposition process is the dynamic balance of surface growth and surface damage.…”
Section: Microstructure Of Dlc Filmsmentioning
confidence: 92%
See 4 more Smart Citations
“…The Ti interlayer exhibits a dense and compact columnar structure from a partially enlarged zone on the bottom left corner of Figure 6C. increases to 0.019 μm at 330 V. It is found that the higher the sp 3 content is, the smaller the surface roughness is. The deposition process is the dynamic balance of surface growth and surface damage.…”
Section: Microstructure Of Dlc Filmsmentioning
confidence: 92%
“…The physical structure and sp 3 /sp 2 ratio of DLC films were characterized using a Renishaw Raman imaging microscope equipped with a 514 nm line of an Argon ion (Ar + ) laser. The laser power on the sample was approximately 2 mW and accumulated for 20 s. X-ray photoelectron spectroscopy (XPS, PHI5000 Versa) was used to analyze the C1s core level spectra and sp 3 working in contact mode. The collection area and pixels of the images were 2 Â 2 μm and 256 Â 256 points.…”
Section: Film Characterizationmentioning
confidence: 99%
See 3 more Smart Citations